Coronary artery disease detected by coronary computed tomography angiography in adult survivors of childhood Hodgkin lymphoma - Daniel A. Mulrooney; Sara Nunnery; Gregory T. Armstrong; Kirsten K. Ness; Deo Kumar Srivastava; Fiona Donovan; Beth A. Kurt; Monika L. Metzger; Matthew J. Krasin; Vijaya M. Joshi; Jean‐Bernard Durand; Leslie L. Robison; et al. (2014)
BACKGROUND Survivors of Hodgkin lymphoma (HL) have significant cardiovascular risk and require long‐term surveillance. The current study assessed the prevalence of coronary artery disease (CAD) by coronary computed tomography angiography (CCTA) in adult survivors of childhood HL. METHODS Thirty‐one survivors of HL, 13 of whom (42%) were treated with radiotherapy (RT) only and 18 of whom (58%) were treated with multimodal therapy, underwent CCTA, echocardiography, electrocardiography (ECG), and treadmill stress testing. Obstructive CAD was defined as ≥50% occlusion of the left main or ≥70% occlusion of the left anterior descending, left circumflex, or right coronary arteries on CCTA. Echocardiograms with resting wall motion abnormalities or an ejection fraction <50%; ECGs with Q waves, ST abnormalities without Q waves, or T‐wave abnormalities without Q waves; and a J‐point depression of ≥1 mm with a horizontal or downsloping ST segment on stress testing were considered abnormal. RESULTS The prevalence of disease in participants (median age, 40 years [range, 26 years‐55 years]; median time from cancer diagnosis, 24 years [range, 17 years‐39 years]) was 39%, with 39 plaques detected among 12 survivors. Three participants (10%) treated with RT only had 4 obstructive lesions; 9 patients (29%; 5 of whom were treated with RT only and 4 of whom were treated with multimodal therapy) had nonobstructive lesions. Approximately 15% of lesions involved the left main, 21% involved the proximal left anterior descending, 18% involved the proximal right coronary, and 13% involved the proximal left circumflex arteries. Of the 12 participants found to have CAD by CCTA, 7 had a positive ECG, 1 had a positive echocardiogram, and 1 had a positive stress test. CONCLUSIONS CCTA identified CAD in a substantial percentage of survivors of HL and may be an effective screening modality for this population. Cancer 2014;120:3536–3544. © 2014 American Cancer Society .